Cost of Goods Manufactured and Optimization of Tapioca Production at PT XYZ in Central Lampung Regency (Case Study at PT XYZ, Central Lampung Regency) - Amanda Putra Seta; Wan Abbas Zakaria; Wuryaningsih Dwi Sayekti (International Journal of Agricultural Sciences, 2020)
.